2021
DOI: 10.1155/2021/5597473
|View full text |Cite
|
Sign up to set email alerts
|

Cryptococcus neoformans Meningoencephalitis in an Immunocompetent Patient after COVID-19 Infection

Abstract: Cryptococcus neoformans is a saprophytic fungus that causes fatal disseminated infections in immunocompromised hosts. Since the onset of the COVID-19 pandemic, multiple cases of secondary viral, bacterial, and fungal infections have been reported in patients after SARS-CoV-2 infection. We describe here a case of severe cryptococcal meningitis that developed in a previously healthy patient one week after treatment of SARS-CoV-2 infection with dexamethasone. This case adds to the growing knowledge of emerging se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 10 publications
2
48
0
1
Order By: Relevance
“…reported a case of a patient with disseminated cryptococcosis diagnosed on day 75 of COVID-19 infection in the setting of a prolonged course of both IV and oral steroids [ 10 ]. A case of cryptococcal meningoencephalitis with absent neurological symptoms is presented by Ghanem and Sivasubramanian [ 11 ]. These two cases highlight the importance of expanding the differential diagnosis to also include superimposed fungal infections in cases of COVID-19 with prolonged hospital courses.…”
Section: Discussionmentioning
confidence: 99%
“…reported a case of a patient with disseminated cryptococcosis diagnosed on day 75 of COVID-19 infection in the setting of a prolonged course of both IV and oral steroids [ 10 ]. A case of cryptococcal meningoencephalitis with absent neurological symptoms is presented by Ghanem and Sivasubramanian [ 11 ]. These two cases highlight the importance of expanding the differential diagnosis to also include superimposed fungal infections in cases of COVID-19 with prolonged hospital courses.…”
Section: Discussionmentioning
confidence: 99%
“…Antifungal agents, including amphotericin B, fluconazole, and 5-flucytosine, are the current approved treatment of cryptococcosis [ 68 ]. Till now, some cases of Cryptococcus infection were reported in COVID-19 patients [ 65 , 69 , 70 ], which one of them was a 60-year-old man who received tocilizumab plus corticosteroids and diagnosed with candidemia and cryptococcemia [ 65 ]. Despite antifungal therapy, the patient died within 10 days of cryptococcemia [ 65 ].…”
Section: Covid-19-associated Opportunistic Infectionsmentioning
confidence: 99%
“…Despite antifungal therapy, the patient died within 10 days of cryptococcemia [ 65 ]. Meningoencephalitis due to C. neoformans was reported in a 73-year-old woman who received azithromycin and dexamethasone after COVID-19 infection [ 70 ]. Other cases were reported from COVID-19 patients with several underlying diseases who received immunosuppressive therapy (e.g., corticosteroids and tocilizumab) [ 24 , 71 – 73 ].…”
Section: Covid-19-associated Opportunistic Infectionsmentioning
confidence: 99%
“…Previous research has shown an association between high levels of IL-6 and resistance to cryptococcal infection [ 104 ]. The most recent case report presented a patient with COVID-19 who was treated with dexamethasone and developed severe cryptococcal meningitis [ 105 ]. The authors suggest that the impact of steroids on T-cell function should be further investigated, as T-cell depletion has been shown to be a driving factor for cryptococcal meningitis.…”
Section: Fungal Coinfectionsmentioning
confidence: 99%